2016
DOI: 10.14236/jhi.v23i3.840
|View full text |Cite
|
Sign up to set email alerts
|

Digital literacy knowledge and needs of pharmacy staff: A systematic review

Abstract: Objective To explore the digital literacy knowledge and needs of pharmacy staff including pharmacists, graduate (pre-registration) pharmacists, pharmacy technicians, dispensing assistants and medicine counter assistants. Methods A systematic review was conducted following a pre-published protocol. Two reviewers systematically performed the reproducible search, followed by independent screening of titles/abstracts then full papers, before critical appraisal and data extraction. Full articles matching the search… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
33
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(35 citation statements)
references
References 13 publications
1
33
0
1
Order By: Relevance
“…A mobile health application was only used in one study [ 55 ], whereas social media was not used in any study. Factors relating to the digital literacy of the pharmacy workforce could be a key issue holding back the use of these tools [ 42 ]. A number of studies have highlighted that while many within the pharmacy workforce had high levels of digital literacy, most did not use technology in their work life [ 65 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A mobile health application was only used in one study [ 55 ], whereas social media was not used in any study. Factors relating to the digital literacy of the pharmacy workforce could be a key issue holding back the use of these tools [ 42 ]. A number of studies have highlighted that while many within the pharmacy workforce had high levels of digital literacy, most did not use technology in their work life [ 65 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, it is important that healthcare professionals develop their own digital literacy skills so that they can support their patients and customers to reap the benefits of technological advances to improve their health. A 2016 systematic review raised concerns about regarding pharmacies supporting the digital training of their workforce [ 42 ]. This review highlighted that while a pharmacy is using technology on a daily basis it does not appear to have adapted a structured training approach or development standards for its workforce.…”
Section: Introductionmentioning
confidence: 99%
“…Berdasarkan hasil wawancara pemanfaatan elektronik digital masih belum maksimal digunakan di area keperawatan Dampak Literasi digital yang kurang menunjukkan rendahnya keterlibatan staf dengan sistem informasi, hal ini berdampak pada lamanya respon pelayanan sehingga bisa berdampak pada kualitas perawatan pasien (MacLure & Stewart, 2016). Penelitian sebelumnya telah mengidentifikasi bahwa tingkat literasi digital yang rendah menunjukkan dampak pada kurangnya keterlibatan staf dengan penggunaan sistem informasi (MacLure & Stewart, 2018).…”
Section: Pembahasanunclassified
“…Strikingly, less than 40% of respondents in the study indicated that they "frequently" or "always" used HITs (eg, accessing patient records and results) as part of their work [39]. Furthermore, a recent systematic review found low levels of digital literacy among pharmacists in Australia, Canada, and the United States [40]. To realize the full potential of HITs, investment is urgently needed in the training and professional development of health care staff to ensure competence and confidence in using HITs, the latter of which has shown to improve engagement with technology [41].…”
Section: Barriers To and Facilitators Of Implementationmentioning
confidence: 99%